2015
DOI: 10.1097/jto.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Recurrence Risk after Curative Resection in Patients with Early-Stage Non–Small-Cell Lung Cancer: A Prospective Cohort Study

Abstract: Background We hypothesized that telomere length in peripheral blood would have significant predictive value for risk of recurrence after curative resection in non-small cell lung cancer (NSCLC). Methods This prospective study included 473 patients with histologically confirmed early stage NSCLC who underwent curative resection at MD Anderson Cancer Center between 1995 and 2008. Relative telomere length (RTL) of peripheral leukocytes was measured by real-time PCR. The risk of recurrence was estimated as hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Weischer and colleagues evaluated lung cancer patients identified from a 20year prospective follow-up of a population-based sample of 47,102 individuals in Denmark (48). Kim and colleagues collected information from 467 lung cancer patients enrolled at MD Anderson Cancer Center in Houston, Texas (60). PBLs are the most common tissue of choice for measuring TL in studies that involve cancer-free individuals and are considered to be an acceptable surrogate for TL in other tissues or organs of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Weischer and colleagues evaluated lung cancer patients identified from a 20year prospective follow-up of a population-based sample of 47,102 individuals in Denmark (48). Kim and colleagues collected information from 467 lung cancer patients enrolled at MD Anderson Cancer Center in Houston, Texas (60). PBLs are the most common tissue of choice for measuring TL in studies that involve cancer-free individuals and are considered to be an acceptable surrogate for TL in other tissues or organs of interest.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, tumor TL can be more heterogeneous and reflect the cumulative impact of many tumor-associated factors that influence telomere homeostasis. Both studies using PBL collected samples prior to treatment, and Weischer and colleagues obtained blood prior to cancer diagnosis (48,60). Therefore, the findings of these studies are unlikely to be confounded by treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some findings showed that shorter telomere length not only increases the risk of gastric cancer, [12] but also decreases the survival rate of bladder cancer, [13] while in other epidemiologic investigates, longer telomere length was associated with the increased risk of cancers that were reported. [1418] To date, little research has investigated the relationship between telomere length and the event of hepatocarcinogenesis (from normal, CHB to HCC) to our knowledge. In this study, the changes of leukocytes telomere length in different cohorts of diseases in a southwest Han Chinese population were investigated to try to understand the relationship of RTL in different stages of hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%